Making the military moral contemporary challenges and responses in military ethics education (Military and defence ethics, 2018)
"This book offers a critical analysis, both theoretical and practical, of ethics education in the military. In the twenty-first century, it has become increasingly important to ensure that the armed forces of Western and other democracies fight justly and behave ethically. The 'good soldier' has to be not only professionally skilled but morally intelligent. At a time of relentless media scrutiny, the publicising of incidents of morally and legally unacceptable behaviour, such as the gross mistreatment of prisoners and the torture of suspected terrorists, can do much to undermine the credibility of those who claim to hold the moral high ground in any particular conflict. Written by an international team of academic theorists and military practitioners, this volume provides inter-disciplinary insights into the present state, and the future, of ethics education in the militaries of Western democracies. The contributors critically address the central question of whether such education is sufficient to prepare members of the armed forces to face the peculiar challenges of conflict environments that are now primarily 'wars among the people', in which the opposing combatants may have little or no regard for human life and fail to discriminate between soldiers and civilians when choosing their targets. Drawing lessons from recent examples of unethical conduct, this original book offers insightful and constructive advice, both theoretical and practical, as to how situations can be improved and on the means that could and should be employed towards this end. This book will be of much interest to students of military studies, ethics and international relations."--Provided by publisher